Dynamic Test Study of Twelve Elastic Constants of Larch Timber - Qiyun Xu; Xinyuan Lan; Muhammad Ali; Yewei Ding; Zheng Wang (BioResources, 2023)
The elastic modulus, shear modulus, and Poisson's ratio of timber are the elastic constants characterizing its material properties. In this paper, the transient excitation method was used to dynamically measure the 10 elastic constants of the falling larch wood under the condition of the free board and cantilever board, that is, 3 elastic moduli E, 3 shear moduli G, and 4 Poisson's ratios μ. The other two Poisson's ratios μ were derived using the principle of orthogonality. At the same time, the elastic modulus, shear modulus, and Poisson's ratio under static conditions were tested and verified by symmetrical four-point bending, asymmetrical four-point bending, and tensile methods. This study is expected to have good application value and practical significance for timber as an engineering structural material, which is widely used in architecture, decoration, furniture, transportation, musical instruments, and in other fields.